Relevance of TNF-α, IL-6 and IRAK1 gene expression for assessing disease severity and therapy effects in tuberculosis patients - Buha, Ivana; Škodrić-Trifunović, Vesna; Adžić-Vukičević, Tatjana; Ilić, Aleksandra; Blanka-Protić, Ana; Stjepanovic, Mihailo; Anđelković, Marina; Vreća, Miša; Milin-Lazović, Jelena; Spasovski, Vesna; Pavlović, Sonja (The Journal of Infection in Developing Countries, 2019)
Introduction: Tuberculosis (TBC) is a contagious chronic respiratory disease which despite the known cause, Mycobacterium tuberculosis (Mtb), and many decades of successful therapy, remains one of the leading global health problems. Immune responses against Mtb infection involve both of types of immunity, but cellular immunity, in which certain cytokines and Th1 cells play a key role, is crucial. A better understanding of the functions of the cytokine network involved in the state and progression of TBC could identify specific molecular markers for monitoring of disease activity as well as therapy outcomes in TBC patients. Methodology: We investigated expression of TNF-α, IL-6 and IRAK1 genes using an RT-qPCR technique in peripheral blood mononuclear cells of 33 TBC patients and 10 healthy individuals. Results: Comparison between TBC patients and healthy individuals revealed statistically significant differences for all analyzed genes. The levels of expression of TNF-α and IL-6 mRNA were higher, while the level of IRAK1 mRNA was lower in the TBC group compared to controls. Moreover, a strong positive correlation was observed between TNF-α and IL-6 gene expression. When clinical parameters were analyzed, increased levels of TNF-α mRNA were detected in patients with a longer duration of therapy (>2 months) compared to those with a shorter therapy duration (< 2 months), and in patients without anemia. Conclusions: Our results indicate that the inflammatory genes we examined play a crucial role in the pathogenesis of tuberculosis, and that the expression of the TNF-α gene could be a marker for monitoring the clinical effect of the ant-tuberculosis drugs during therapy.